2017
DOI: 10.3892/ol.2017.5994
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cathepsin B by the CXCR3 chemokines CXCL9 and CXCL10 in human breast cancer cells

Abstract: Cathepsin B (CTSB) is a lysosomal cysteine protease that has been linked to the progression of breast cancer, for example by activation of other proteases and tumor-promoting cytokines, thereby supporting tumor invasion and metastasis. Previously, it was shown that CTSB cleaves and inactivates C-X-C motif chemokine receptor 3 (CXCR3) chemokines. As CXCR3 ligands have been demonstrated to induce proteases in cancer cells, the present study hypothesized that they may also affect CTSB in breast cancer cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Bannoud et al (2018) found that Cathepsin D can bind the M6PR and are co-transported in an estradiol stimulatory manner through MCF-7 cells and which linked Cathepsin D trafficking with estradioldependent EMT progression (and possible chemoresistence) [145]. Additionally, chemokines CXCL-9 and −10 were seen to upregulate Cathepsin B expression and secretion in BC cells via CXCR3 signaling [146], while the tumour suppressor Protilin was identified as a novel substrate for Cathepsin Z/X, the cleavage of which reduced its binding to Clathrin, thus linking Cathepsin Z/X activity and regulation of Clathrin-dependent endocytosis [147]. Recently, Shao et al (2018) showed that NEDD4 was needed for EGFR-dependent lung cancer cell migration and EGF-induced Cathepsin B secretion, as seen from a lack of Cathepsin B secretion in analysing a ligasedead mutant of NEDD4 and in NEDD4 knockdown experiments [148].…”
Section: Signal Transduction Intermediates and Cathepsin Regulationmentioning
confidence: 97%
“…Bannoud et al (2018) found that Cathepsin D can bind the M6PR and are co-transported in an estradiol stimulatory manner through MCF-7 cells and which linked Cathepsin D trafficking with estradioldependent EMT progression (and possible chemoresistence) [145]. Additionally, chemokines CXCL-9 and −10 were seen to upregulate Cathepsin B expression and secretion in BC cells via CXCR3 signaling [146], while the tumour suppressor Protilin was identified as a novel substrate for Cathepsin Z/X, the cleavage of which reduced its binding to Clathrin, thus linking Cathepsin Z/X activity and regulation of Clathrin-dependent endocytosis [147]. Recently, Shao et al (2018) showed that NEDD4 was needed for EGFR-dependent lung cancer cell migration and EGF-induced Cathepsin B secretion, as seen from a lack of Cathepsin B secretion in analysing a ligasedead mutant of NEDD4 and in NEDD4 knockdown experiments [148].…”
Section: Signal Transduction Intermediates and Cathepsin Regulationmentioning
confidence: 97%
“…Finally, GAGs promote chemokine oligomerization preserving them by proteolytic cleavage and modulating chemokine-receptor linking [ 31 ]. Proteolytic cleavage can occur at either N- or C-terminal region by several proteases [ 32 ], including metalloproteases [ 33 ], dipeptidyl peptidase 4 (DPP4) [ 34 ] or cathepsin B [ 35 ]. Cleaved chemokines can display either reduced or increased activity, or different receptor selectivity.…”
Section: Regulation Of Chemokine Expression and Effectsmentioning
confidence: 99%
“…induce Cathepsin B in human breast cancer cells, thereby supporting tumor invasion and metastasis [21].…”
Section: Discussionmentioning
confidence: 99%